CSIG-34. PI3 KINASE PATHWAY ACTIVATION PROMOTES MALIGNANT PROGRESSION IN OLIGODENDROGLIAL TUMORS. (5th November 2018) - Tateishi, Kensuke; Nakamura, Taishi; Fink, Alexandria; Lelic, Nina; Matsushita, Yuko; Koerner, Mara; Murata, Hidetoshi; Ichimura, Koichi; Batchelor, Tracy; Yamamoto, Tetsuya; Chi, Andrew; Iafrate, John; et al.
Abstract: Oligodendroglioma (OD) is a subtype of adult diffuse glioma defined by IDH1/2 gene mutation and co-deletion of chromosomal arms 1p and 19q. Although prognosis in OD tumors is initially relatively favorable, the majority of OD develop outgrowth of a subclone that has undergone malignant transformation. Modeling the molecular mechanisms of this tumor progression is crucial to identify therapeutic targets for malignant disease. However, there are few available patient-derived OD xenograft models, which limit preclinical investigations. Here, we present novel patient derived anaplastic oligodendroglioma (AOD) xenograft models. In a panel of OD at different stages of disease, we harvested two distinct cell samples: those with and without PIK3CA mutation. From the tumor that subsequently rapidly progressed and had a PIK3CA mutation, we established a xenograft model that was lethal to the mouse and retained the PIK3CA mutation. In contrast, xenograft did not form from the other tumor that was clinically stable after resection and had wild-type PIK3CA . We confirmed AOD phenotype and the presence of IDH1 mutation and 1p/19q co-deletion in xenograft tissue, indicating successful capture of these signature OD genetic alterations. We also tested to see if PI3K/AKT/mTOR gene mutation could induce patient-derived OD xenograft formation. In our attempts to establish xenograft models, the presence of activating mutations in PI3K/AKT/mTOR pathway was consistently associated with successful xenograft establishment. OD/AOD tumors that did not form xenograft did not have mutation in the PI3K/AKT/mTOR pathway Importantly, we found progressive tumor cells that harbor mutant PIK3CA were vulnerable to alkylating agents and PIK/AKT/mTOR pathway inhibitors. These findings suggest there is a critical role of PI3K/AKT/mTOR pathway activation in driving progression and xenograft formation in oligodendroglial tumors. Our xenograft models will facilitate dissection of the mechanism of malignant transformation, contributing to the identification of optimal therapeutic strategies for patients with oligodendroglial tumors